Why should we restrain the availability of paracetamol - an analysis of acetaminophen intoxication in adolescents - Weronika Sosnowska; Aleksandra Brzozowska; Michał Tchórz; Kalina Taracha; Rafał Tkaczyk; Jakub Tomczyk; Maciej Tomkiewicz; Maria Środoń; Gabriela Świątek (Kazimierz Wielki University, 2023)
Introduction and aim: Paracetamol (acetaminophen) is a commonly used analgesics and antipyretics and it is a nonprescription medicine. Improper use of it may lead to accidental or intentional poisoning. The aim of the study was to analyse paracetamol poisonings in children and adolescents admitted to the Clinical Department of Toxicology and Cardiology in Stefan Wyszyński Regional Specialist Hospital in Lublin in 2022. Material and methods: The research was retrospective. Medical records of poisoning cases in patients up to the age of 18 were analysed specifically emphasizing acetaminophen poisonings. Results: In the studied period 120 adolescents were hospitalized due to intoxication, 65 of them due to medications intake, the most commonly used medicine was acetaminophen. There were 20 cases of hospitalization because of acetaminophen intake, 17 (85%) patients were female and 3 (15%) of them were male. Patients were from 15 to 17 years old. In 12 cases (60%) patients came from urban areas. The intentional intoxications were found in 18 (90%) cases, 13 of them were suicide attempt. Majority of cases of attempted suicide were female (92%). The other intoxications were accidental, where patients took acetaminophen as a painkiller. In the researched group there were no deaths. Conclusions: Paracetamol overdosing is always associated with the risk of liver damage.This medicament as a potentially hepatotoxic drug should not be sold over the counter. The availability of paracetamol is too widespread, which poses a risk especially to children and adolescents. The ubiquitous advertising of acetaminophen products as well as their popular use, for example, in menstrual pain, favor their presence in almost every Polish home. Parents and guardians should be educated about the dangers of uncontrolled use of so-called OTC drugs - incorrectly commonly considered safe.